(untitled) (Jurnal Sosiologi Reflektif, 2016)
Institutionally, the Indonesian National Military (TNI) in the New Order era dominated the social and political system in Indonesia. The domination ended by the falling of the Soeharto regime and the emergence of the Reformation era. Nevertheless, the TNI has not undertaken cultural reformation especially on the military-cultural personnel although institutionally it has done so. On the military-cultural personnel aspect, the TNI personnel culture is still dominated by the long-existing feudalistic. This work, therefore, focuses on the practices of discipline, loyalty and militancy as the three basics of the culture of the TNI personnel. To discuss the issue, this project employs the agency and structure of Anthony Giddens and habitus of Pierre Bourdieu theories for analytical purposes.